Psychology in Latin America: A Qualitative Study of Commonalities and Singularities - Consoli, Andrés; Flores, Iliana; Sharma, Himadhari; Sheltzer, Joshua; Gallegos, Miguel; Pérez-Acosta, Andrés (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2021)
Psychology in Latin America, its development, and main contributors have not received the attention they deserve among the scientific and professional English-speaking communities. The present study analyzes the contributions to psychology in Latin America made by the recipients of the Interamerican Psychology award in the Spanish or Portuguese category, granted by the Interamerican Society of Psychology. The award, instituted in 1976 and named Rogelio Díaz Guerrero since 2007, recognizes psychologists who have advanced the discipline as a science and profession in the Americas. To date, SIP has granted 26 such awards. This qualitative study identifies commonalities and singularities in the contributions made by the first 26 awardees. The commonalities were organized around three overlapping themes: social responsiveness, intersectionality of psychology and culture, and international engagement. The singularities were systematized into two overlapping themes: development of historically underdeveloped topics, and discipline transformations. Each theme is defined and illustrated accordingly. The commitment to advancing social justice and increasing the relevance of psychology in addressing social issues by the awardees as a whole stands out as an important characteristic of psychology in Latin America.